2016
DOI: 10.1016/j.ijrmhm.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of penetration performance and penetration mechanism of w-cu shaped charge liner against three kinds of target: Pure copper, carbon steel and Ti-6Al-4V alloy

Abstract: In order to investigate the interaction between shaped charge jet and target, three different targets, including pure copper target, carbon steel target and Ti-6Al-4V alloy target, were penetrated by W-Cu shaped charge jet. Penetration performance and corresponding penetration mechanisms were studied. Calculated theoretical penetration depth ratio of Ti-6Al-4V alloy target, pure Cu target and carbon steel target is 10:2.8:5.7, while the practical penetration depth ratio is 10:28:21, indicating that the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…The penetration depth of a shaped charge jet is the dominant criterion for evaluating jet performance. Studies on the microstructure of penetrated targets have illustrated the mechanism of jets interacting with targets by observing the representative zone of target materials [ 21 , 22 ]. However, few studies have compared the jet performance of SLM-produced liners and machined liners and further details remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The penetration depth of a shaped charge jet is the dominant criterion for evaluating jet performance. Studies on the microstructure of penetrated targets have illustrated the mechanism of jets interacting with targets by observing the representative zone of target materials [ 21 , 22 ]. However, few studies have compared the jet performance of SLM-produced liners and machined liners and further details remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Improved mechanical properties were verified by static compression and split Hopkinson pressure bar test. The interaction of Cu-W jet with the target material was investigated in [53]. For this reason, three target materials Cu, carbon steel, and Ti-6Al-4V alloy were selected for penetration.…”
Section: Materials For the Liner Of Shaped Chargementioning
confidence: 99%
“…Research has shown that increasing the jet density ρ j and length l can effectively improve the penetration ability of the jet [3]. To further improve the damage ability of an SCJ warhead to an armored target, researchers [4][5][6][7][8][9][10] tried to prepare a W-Cu material to replace the existing pure copper material and increase the jet density; however, Lee [11] found that the contribution of W to the total deformation of a W-Cu jet was very limited. The W-W boundary of W-Cu alloys was prone to fracture during tensile deformation, which limited penetration performance of a W-Cu jet at large stand-off.…”
Section: Introductionmentioning
confidence: 99%